2017
DOI: 10.1016/j.hemonc.2017.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality therapy improves survival in intramedullary spinal cord metastasis of lung primary

Abstract: Lung cancer is the predominant cause of intramedullary involvement of the spinal cord. Overall prognosis is poor, although a multimodality approach was associated with improved survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 51 publications
0
6
0
2
Order By: Relevance
“…[5,8,12] Although chemotherapy is uniformly utilized, surgery is performed in 31% of cases along with adjuvant radiotherapy. [3,9,11,12,13,15] In our patient, as the systemic evaluation revealed a primary RCC, it was most likely that the intramedullary C1-C2 lesion was a metastasis.…”
Section: Discussionmentioning
confidence: 71%
“…[5,8,12] Although chemotherapy is uniformly utilized, surgery is performed in 31% of cases along with adjuvant radiotherapy. [3,9,11,12,13,15] In our patient, as the systemic evaluation revealed a primary RCC, it was most likely that the intramedullary C1-C2 lesion was a metastasis.…”
Section: Discussionmentioning
confidence: 71%
“…Moreover, immunotherapy may play a role in the treatment in the future [31]. While all these modalities on their own may play an essential role in the management of these lesions, a recent review showed favorable survival in patients receiving a multimodal treatment [17]. However, these results were only shown in patients with metastatic lung cancer, which limits the significance for intramedullary metastases of other tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Given the scarcity of intramedullary metastases, highlevel evidence and guidelines on their management are lacking. Current treatment options include microsurgical resection, chemotherapy, fractionated radiotherapy and stereotactic radiosurgery (SRS) as well as a combination of them [2,[15][16][17]. In recent years, several studies have been published on the efficacy of surgery and radiotherapy for local control and their effect on neurological deficits [5,[18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, oligometastatic patients in whom the primary pathology is controlled [ 19 , 20 ], and with significant or complete neurological deficits are managed surgically [ 1 , 21 ]. In our review, the tumor volume of treated IMMs averaged 0.9 cc [ 13 , 15 17 ].…”
Section: Discussionmentioning
confidence: 99%